Adapting the quinoa (Chenopodium quinoa Willd.) to cultivation in the brazilian highlands: preliminary results - Spehar, Carlos Roberto; de Souza, Plínio Itamar de Mello (Pesquisa Agropecuaria Brasileira, 1993)
The quinoa, a pseudocereal originated from the Andes, has performed an important role to the civilizations of that part of the world, mainly due to the high biological value of its protein. The species is sensitive to changes in photoperiod and temperature, which turns its adaptation to the Tropics dependent on the acquisition of adapted genotypes. The present work aims to present it as an alternative for the production systems in the cerrados. The Embrapa-Centro de Pesquisa Agropecuária dos Cerrados (CPAC), started a breeding program by individual selection in a late breeding population from temperate zones. The results, as measured by plant cicle, plant height and yield, are promising and stimulate further selection of genotypes to fully adapt it into cultivation in the highlands of Central Brazil.